Pengaruh Rasio Keuangan Daerah terhadap Alokasi Belanja Modal Pemerintah Provinsi di Pulau Sumatera Tahun 2019-2023 - Rahmadani, Dona Tasyati; Fimansyah, Fimansyah; Hartaty, Sri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The background of this research is based on the condition of capital expenditure allocation management in the provinces of Sumatra Island, which has not yet reached an optimal level. The objective is to analyze the influence of the Regional Financial Ratio on capital expenditure allocation. Effective PAD management is important to reduce dependence on debt and ensure the sustainability of infrastructure financing. Excessive dependence on short-term debt has the potential to create fiscal risks, so efficient financial management is needed to maintain liquidity stability and long-term investment. The type of data used is secondary data in the form of financial reports. The analysis was conducted using a purposive sampling approach and panel data regression using Eviews 12 software. The results of the adjusted R2 analysis with a value of 0.540432 indicate that 54% of the variation in Capital Expenditure Allocation can be explained through the contribution of the Degree of Decentralization Ratio, Regional Financial Efficiency Ratio, and Liquidity Ratio. For future research, it is recommended to include additional independent variables and increase the number of research samples to expand the scope of the empirical analysis.